EFEKTIVITAS PENGGUNAAN MEDIA SCRAPBOOK PADA KETERAMPILAN MENULIS NARASI SISWA KELAS VI SEKOLAH DASAR - Tri Widiastuti (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This research is motivated by the low skills of students in writing narratives. This study aimed to describe the effectiveness of using Scrapbook media on the narrative writing skills of sixth-grade elementary school students. This research uses a descriptive qualitative research method. This study’s subjects were sixth-grade elementary school students of SD 1 Jepang. The sampling technique used is purposive sampling, which uses the entire sixth grade, which consists of 32 students. Data collection techniques using observation, interviews, and documentation. Data analysis techniques in research take place before in the field and during the field. The results showed that it was easier for students to write narratives using Scrapbook media. Interest in learning also increases with the use of these media. In addition, students' narrative writing learning outcomes also increased to an average of 75. From the results of this study, it can be concluded that Scrapbook media is effectively used in the narrative writing skills of sixth-grade elementary school students.